Nutrimental, physicochemical and sensory properties of creole avocado fruits from Parras de la Fuente, Coahuila - Chávez-García, Stephany Nefertari; De León-García, Patricia Guadalupe; Campos-Múzquiz, Lizeth Guadalupe; Flores-Gallegos, Adriana Carolina; Castillo-Godina, Rocío Guadalupe; Ascacio-Valdes, Juan Alberto; Lopez-Badillo, Claudia Magdalena; Rodríguez-Herrera, Raúl (Ecosistemas y Recursos Agropecuarios, 2024)
The city of Parras de la Fuente, Coahuila is characterized by having criollo avocado trees with different morphological properties. However, very little information is available on their fruit nutritional and sensory characteristics. The objective of this work was to perform the bromatological, mineral, phytochemical and sensory characterization of 7 avocado landraces. The proximal analysis was carried out using standardized tests by the AOAC (2019), while the phytochemical content was determined using HPLC/MS equipment. Subsequently, the samples were evaluated using a hedonic test. The bromatological analysis showed significant differences in the total of the samples for the different response variables, which indicates the great genetic diversity among the sampled trees. The mineral that were determined in the highest concentration were Potassium, Magnesium and Calcium. Thirty-eight different phytochemical compounds were identified in the fruits, with a greater presence of flavones. While the sensory analysis showed a significant difference among the avocado landraces for the evaluated attributes. The flavor and texture attributes were the most important for the consumer preference. Different environmental factors (soil, climate, altitude, latitude, maturity) modify the nutritional composition of the avocado and its organoleptic characteristics. The results of this work may help propagation, fruit diversification and development of companies focused on this fruit in Parras de la Fuente, Coahuila.
Keywords: Persea americana Mill.; nutritional properties; sensory properties; phytonutrients